Acute peritoneal dialysis in the treatment of COVID-19-related acute kidney injury - Ponce, Daniela [UNESP] (2020)
The kidney is not typically the main target of severe acute respiratory syndrome coronavirus 2, but surprisingly, acute kidney injury (AKI) may occur in 4-23% of cases, whereas the dialysis management of AKI from coronavirus 2019 has not gained much attention. The severity of the pandemic has resulted in significant shortages in medical supplies, including respirators, ventilators and personal protective equipment. Peritoneal dialysis (PD) remains available and has been used in clinical practice for AKI for >70 years; however, it has been used on only a limited basis and therefore experience and knowledge of its use has gradually vanished, leaving a considerable gap. The turning point came in 2007, with a series of sequential publications providing solid evidence that PD is a viable option. As there was an availability constraint and a capacity limit of equipment/supplies in many countries, hemodialysis and convective therapies became alternatives. However, even these therapies are not available in many countries and their capacity is being pushed to the limit in many cities. Evidence-based PD experience lends support for the use of PD now.